The Effectiveness of Integrated Komsiga Media on Islamic Education Values in Improving Science Literacy among Elementary School Students - Mawaddah Warohmah; Mega Setya Handayani; Ely Mufidah (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
The science literacy score of Indonesian students is 383, far below the OECD average of 485 (OECD, 2023). This low score is due to IPAS learning process being considered abstract and difficult to understand. There is an urgent need for innovative media that not only visualizes scientific concepts concretely but also instills character values to bridge the cognitive and affective gaps among students. This study aims to examine the effectiveness of Komsiga media, which integrates Islamic educational values, in improving students' science literacy skills in the subject of Force. The study applied a quantitative approach with a one-group pretest-posttest pre-experimental design involving 30 fourth-grade elementary school students as the sole participants. The data were analyzed statistically using the mean difference test and Normalized Gain. The findings show a significant increase in learning outcomes, with the average student score jumping from 63.80 on the pre-test to 87.23 on the post-test. The N-Gain score of 0.65, which falls into the moderate category, confirms that Komsiga integrated with Islamic educational values is able to make science material easier to understand and more relevant to students. Komsiga has been proven to be effective as a bridge for conceptual understanding and character building. This study recommends that this model of integrating technology and values be expanded to other IPAS topics to support holistic learning. Keywords: digital comics, komsiga, science literacy, IPAS learning, islamic educational values